Physiologic and immunologic effects of subxiphoid pulmonary lobectomy compared with transthoracic pulmonary lobectomy in a canine survival model - Wen, Chih-Tsung; Chu, Yen; Wu, Yi-Cheng; Hsieh, Ming-Ju; Liu, Chien-Ying; Liu, Chia-Chuan; Ko, Po-Jen; Liu, Yun-Hen; Liu, Hui-Ping (Journal of Thoracic Disease, 2015)
Background: Subxiphoid thoracoscopic surgery has been used in various thoracic surgical procedures. The aim of this study is to compare the physiological and inflammatory responses between subxiphoid thoracoscopic surgery and standard transthoracic thoracoscopic surgery for anatomic pulmonary lobectomy in a canine model. Methods: Nineteen dogs were assigned to subxiphoid (n=10) or standard thoracoscopy (n=9). Animals in the subxiphoid and standard thoracoscopy group received anatomic lobectomy via a 3-cm xiphoid and thoracic incision, respectively. Physiological and inflammatory parameters were compared between the two groups before surgery, during the operation, and on postoperative days 1, 3, 7, and 14. The animals were sacrificed and necropsied at 2 weeks after surgery. Results: All procedures were performed successfully with no conversion nor complication. The physiologic changes were similar in both groups. There was no observable different between the two groups in terms of C-reactive protein (CRP) level, interleukin-6 (IL-6) level, neutrophil count, neutrophil 20,70-dichlorodihy drofluorescein (DCFH) expression, monocyte count, monocyte inducible nitric oxide synthase (iNOS), and CD4/CD8 ratios. However, the reduction of total lymphocyte count, CD4, and CD8 lymphocyte counts were observed in the subxiphoid anatomic lobectomy group on postoperative day 7, which was significantly lower than that of the standard transthoracic thoracoscopic approach. Conclusions: Subxiphoid thoracoscopic surgery resulted in similar physiologic impact and surgical outcome to those of standard transthoracic thoracoscopic surgery. Nevertheless, subxiphoid thoracoscopic surgery is associated with more pronounced immunosuppression than the standard transthoracic thoracoscopic approach.